Molecular characterization of NSCL, a gene encoding a helix-loop-helix protein expressed in the developing nervous system. - Begley, C G (1992)
We report here the molecular cloning and chromosomal localization of an additional member of the helix-loop-helix (HLH) family of transcription factors, NSCL. The NSCL gene was identified based on its hybridization to the previously described hemopoietic HLH gene, SCL. Murine NSCL cDNA clones were obtained from a day 11.5 mouse embryo cDNA library. The coding region is 399 base pairs and encodes a predicted protein of 14.8 kDa. The nucleotide sequence shows 71% identity and the amino acid sequence shows 61% identity to murine SCL in the HLH domain. The NSCL protein-coding region terminates six amino acids beyond the second amphipathic helix of the HLH domain. Expression of NSCL was detected in RNA from mouse embryos between 9.5 and 14.5 days postcoitus, with maximum levels of expression at 10.5-12 days. Examination of 12- and 13-day mouse embryos by in situ hybridization revealed expression of NSCL in the developing nervous system. The NSCL gene was mapped to murine chromosome 1. The very restricted pattern of NSCL expression suggests an important role for this HLH protein in neurological development.